Acute myeloid leukemia drug tolerant persister cells survive chemotherapy by transiently increasing plasma membrane rigidity, that also increases their sensitivity to immune cell killing - Yael Morgenstern; JongBok Lee; Yoosu Na; Brandon Y. Lieng; Nicholas S. Ly; William D. Gwynne; Rose Hurren; Li Ma; Dakai Ling; Marcela Gronda; Andrea Arruda; Avraham Frisch; et al. (Haematologica)
Resistance to chemotherapy remains a major hurdle to the cure of Acute Myeloid Leukemia (AML) patients. Recent studies indicate a minority of malignant cells, termed drug-tolerant persisters (DTPs), stochastically upregulate stress pathways to evade cell death upon acute exposure to chemotherapy without acquiring new genetic mutations. This chemoresistant state is transient and the cells return to baseline after removal of chemotherapy. Yet, the mechanisms employed by DTPs to resist chemotherapy are not well understood and it is largely unknown whether these mechanisms are also seen in patients receiving chemotherapy. Here, we used leukemia cell lines, primary AML patient samples and samples from patients with AML receiving systemic chemotherapy to study the DTP state. We demonstrated that a subset of AML cells transiently increases membrane rigidity to resist killing due to acute exposure to Daunorubicin and Ara-C. Upon removal of the chemotherapy, membrane rigidity returned to baseline and the cells regained chemosensitivity. Although resistant to chemotherapy, the increased membrane rigidity, rendered AML cells more susceptible to T-cell mediated killing. Thus, we identified a novel mechanism by which DTP leukemic cells evade chemotherapy and a strategy to eradicate these persistent cells.